2017
DOI: 10.1589/jpts.29.1377
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the function, activity and participation and quality of life between down syndrome children and typically developing children

Abstract: [Purpose] To compare function, activity, participation, and quality of life of Down syndrome children and typically developing children according to age. [Subjects and Methods] A total of 16 Down syndrome children and 20 children with typical development were included as subjects for this study. International Classification of Functioning, Disability, and Health (ICF) Child and Youth version (CY) developed by the World Health Organization (WHO) and a questionnaire were used to measure children’s functioning, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
2
12
0
3
Order By: Relevance
“…Given the aforementioned characteristics and support needs specific to people with DS, it is critical to better understand and measure QoL in this population. Most studies have focused on family QoL (Marchal, Maurice-Stam, van Trotsenburg, & Grootenhuis, 2016;Vadakedom et al, 2017) or health-related QoL (Graves et al, 2016) and found significantly poorer scores for youth with DS in comparison with normative data (Haddad, Bourke, Wong, & Leonard, 2018;Jung, Chung, & Lee, 2017;Rofail et al, 2017;Shields et al, 2018;Xanthopoulos et al, 2017). Yet individual QoL is a broader and more comprehensive construct that is not merely reduced to health-related wellness as other important domains and indicators that are relevant for children with DS need to be articulated in order to develop comprehensive interventions (Murphy et al, 2017;Newton, 2018).…”
mentioning
confidence: 99%
“…Given the aforementioned characteristics and support needs specific to people with DS, it is critical to better understand and measure QoL in this population. Most studies have focused on family QoL (Marchal, Maurice-Stam, van Trotsenburg, & Grootenhuis, 2016;Vadakedom et al, 2017) or health-related QoL (Graves et al, 2016) and found significantly poorer scores for youth with DS in comparison with normative data (Haddad, Bourke, Wong, & Leonard, 2018;Jung, Chung, & Lee, 2017;Rofail et al, 2017;Shields et al, 2018;Xanthopoulos et al, 2017). Yet individual QoL is a broader and more comprehensive construct that is not merely reduced to health-related wellness as other important domains and indicators that are relevant for children with DS need to be articulated in order to develop comprehensive interventions (Murphy et al, 2017;Newton, 2018).…”
mentioning
confidence: 99%
“…In particular, interventions and support to the whole family are important and can positively impact a family and a child's quality of life. [10][11][12][13][14][15][16][17] Because support for children and families is crucial to their present daily living and their future, we wanted to find ways to improve relationships between families and services to connect them, the hospital setting, and health services in the community. This included providing ways for parents to identify disability in their own children and thus enter into a dialogue to build a mutual understanding of disability.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, interventions and support to the whole family are important and can positively impact a family and a child’s quality of life. 10 17…”
Section: Discussionmentioning
confidence: 99%
“…Pada penelitian Hee Kyoung tahun 2017 menyebutkan bahwa anak tunagrahita khususnya dengan tipe klinis down syndrome memiliki kekurangan dalam fungsi eksekutif, tingkat memori dan kognitif yang rendah, inisiasi dan penekanan respon kurang, serta kurangnya kemampuan dalam pemecahan masalah dan perencanaan. Oleh karenanya dapat mempengaruhi dimensi kognitif dan sekolah pada anak (Jung et al, 2017).…”
Section: Dimensi Lingkunganunclassified